Global supply chain resilience with the flexible partnership - Aluisius Hery Pratono; Ling Han; Asri Maharani (Modern Supply Chain Research and Applications, 2023)
Purpose - This paper aims to examine how multinational corporations respond to environmental turbulence by adopting a flexible supply chain (SC). Design/methodology/approach - This study adopts a case study in the medical industry to identify effective strategic approaches by taking advantage of new business opportunities and navigating complex business partnerships. This study focuses on medical diagnostic equipment, including computed tomography, magnetic resonance imaging and X-ray, that involves the suppliers, channel partners and medical users. Findings - (1) The market turbulence brought the SC leaders to adopt multiple partnership approaches, i.e. funnel-based and area-based partnerships. (2) Adopting a funnel-based partnership allows the SC to seize new market opportunities. Still, it brought a risk element of SC failure from the flawed selection process and professional misconduct. (3) SC leaders adopted flexible partnerships to help address the risk of professional misconduct and select partners for long-term collaboration. Originality/value - This paper contributes to emergent literature on social exchange theory by exposing the global SC when the SC leaders set up agility approaches. This paper also extends the discussion on the industrial marketing and purchasing theory, which seeks to promote an active buyer-seller relationship.
Keywords: 650; COVID-19; Global supply chain; Medical equipment; Resilience